翻译与国家发展需求的改变 ：以新加坡政府中小学的英文命名及中文译名为例 = Translation and national development : a study on the bilingual names of government primary and secondary schools in Singapore - 李佳颖 Lee, Jia Ying (2019)
新加坡自英殖民时期便是多元种族的社会，而新加坡尤其在1965年国家独立后更加地重视种族和谐的问题。比如，政府将新加坡四大族群的语言都设为国家的官方语言，同时也根据官方语言中的中文、马来文及淡米尔文逐渐为公共设施添置英文以外的译名。当中，便包括了新加坡政府中小学的英文命名及中文译名。随着时代的变迁、国家的发展以及新政策的实行，这些学校的命名与中文译名的翻译规律同时也跟着改变。本篇论文将结合新加坡的历史与政治脉络，从而分析不同时期的国家政策与发展需求是如何影响政府中小学的英文命名与中文译名。同时，本文也将探讨采用意译、音译、直译等翻译方式的中文校名，从而了解学校名称一再变迁的意义。Singapore started out as a multiracial society ever since her British colonial times back in the 1800s to mid-1900s, and the government started to pay more attention to the topic of racial harmony especially after Singapore’s independence in 1965. To tackle the problem of racial issue, the Singapore government set the official languages of the country to accommodate to the four major races, namely Chinese, Malay and Tamil, with English as the de facto language of Singapore. Soon after, apart from the English naming, translations of the three other languages could also be seen in the names of the country’s public amenities, amongst which included the English name and Chinese translated name of government primary and secondary schools. Along with the developments of the country as well as the implementation of new government policies, the naming of these government schools also started to have a shift in naming pattern. This paper would firstly analyse Singapore’s history and political context, then examine Singapore’s government policies and development needs to understand how these factors affect the English name and Chinese translated name of government primary and secondary schools. At the same time, this paper would take into consideration the different translation methods that were used in the Chinese translation of the school names, namely Transliteration, Free Translation, Literal Translation, etc. and thereafter find out the significance behind the constant changes of these school names.